Breastfeeding at the workplace: a systematic review of interventions to improve workplace environments to facilitate breastfeeding among working women - Mireya Vilar-Compte; Sonia Hernández-Cordero; Mónica Ancira-Moreno; Soraya Burrola-Méndez; Isabel Ferre-Eguiluz; Isabel Omaña; Cecilia Pérez Navarro (BMC, 2021)
Abstract Background Breastfeeding can be affected by maternal employment. This is important considering that in 2019, 47.1% of women globally participated in the labor force. The aim of this study was to review workplace interventions to promote, protect and support breastfeeding practices among working mothers globally. Methods A systematic review was conducted following the guidance of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Observational, experimental and qualitative peer-reviewed studies in English and Spanish, published between 2008 and 2019 were included. The review focused on working women who were pregnant, breastfeeding or who recently had a child, and women's working environments. The outcomes of interest included breastfeeding intentions, initiation, exclusivity and duration, confidence in breastfeeding or breastmilk extraction, and perceived support at workplace. Quality was assessed according to National Institute for Health and Care Excellence (NICE) checklist for systematic reviews. It was registered on PROSPERO (#140624). Results Data was extracted from 28 quantitative and 9 qualitative studies. The most common interventions were designated spaces for breastfeeding or breastmilk extraction (n = 24), and the support from co-workers (n = 20). The least common interventions were providing breast pumps (n = 4) and giving mothers the flexibility to work from home (n = 3). Studies explored how interventions affected different breastfeeding outcomes including breastfeeding duration, breastfeeding exclusivity, confidence in breastmilk expression, and breastfeeding support. The evidence suggests that workplace interventions help increase the duration of breastfeeding and prevent early introduction of breastmilk substitutes. Having a lactation space, breastmilk extraction breaks, and organizational policies are key strategies. However, to achieve equitable working conditions for breastfeeding mothers, organizational and interpersonal changes need to occur as well. Conclusions The systematic review revealed that interventions at the workplace are important in protecting, promoting and supporting breastfeeding among working mothers. To achieve equitable work environments and fair nutritional opportunities for infants of working mothers, interventions should focus at the three ecological layers - individual, interpersonal, and organizational. The quality of studies can be improved. There is a need for studies assessing impacts of workplace interventions on infant feeding practices, mothers' self-esteem and outcomes such productivity and abstentionism.